2018
DOI: 10.1016/j.cmet.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Artemether Does Not Turn α Cells into β Cells

Abstract: Pancreatic α cells retain considerable plasticity and can, under the right circumstances, transdifferentiate into functionally mature β cells. In search of a targetable mechanistic basis, a recent paper suggested that the widely used anti-malaria drug artemether suppresses the α cell transcription factor Arx to promote transdifferentiation into β cells. However, key initial experiments in this paper were carried out in islet cell lines, and most subsequent validation experiments implied transdifferentiation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 33 publications
4
54
1
Order By: Relevance
“…Li et al (20) reported that artemisinin can drive a cells into functional b-like cells through enhanced GABA signaling. But 2 subsequent papers failed to replicate this finding (21,22). These discrepancies could be due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (20) reported that artemisinin can drive a cells into functional b-like cells through enhanced GABA signaling. But 2 subsequent papers failed to replicate this finding (21,22). These discrepancies could be due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the immune system, Li et al (20) reported that AS might have a role in promoting the transdifferentiation of a to b cells. However, this finding has been challenged (21,22).…”
mentioning
confidence: 99%
“…This leads to activation of the PI3K/Akt pathway and the enhancement of b-cell replication and survival (11,22,27,75,76). The increased b-cells are unlikely to arise from the transdifferentiation of human islet a-cells into b-cells because 1) that was observed only after long-term GABA treatment (2-3 mo, as opposed to the 10-d treatment period in our xenograft studies) (66,67), and 2) those observations have been called into question by others (77,78) as well as by our observations in mice given combination therapy (discussed above).…”
Section: Discussionmentioning
confidence: 73%
“…The authors purported that artemisinins, including artemether, increase GABA signaling and prevent glucagon secretion by α-cells, resulting in their consequent loss of identity and transdifferentiation to a βlike phenotype, with associated increased insulin content and improvement in GSIS assessments [76]. However, follow up reports challenged these results, showing that neither artemisinins nor GABA directly cause α-to β-cell conversion [77,78].…”
Section: The Genetic Makeup Of β-Cells Defines Their Functionmentioning
confidence: 99%